Knowledge and consumption practices on sugar-sweetened beverages and its relation to the BMI among selected College of Home Economics students of the University of the Philippines - Diliman - Angeles, Sophia Therese; De Mesa, Aldwin Cedri; Montuya, Lorenyz Rafael
Obesity is characterized by a positive energy balance due to the excess intake of energy-dense food. One such class of food items is sugar-sweetened beverages (SSB). While there is a clear association between obesity and excessive SSB consumption, there is conflicting information concerning the association of knowledge of SSBs to obesity. This study investigated the association between knowledge and consumption practices on SSBs to the BMI and Waist-to-Hip Ratio (WHR) of selected UP Diliman College of Home Economics (CHE) students. In-person recruitment, posting of media cards within the grounds of CHE, and calls for participants through Facebook posts were conducted to hire potential participants. Thirty participants were recruited for this study through convenience sampling. Knowledge was measured through the Sugar-sweetened Beverage Knowledge Questionnaire (SSBKQ) while consumption practices were determined using the Beverage Questionnaire - 15 (BEVQ-15). Anthropometric data were measured at the CHE-DFSN Nutrition Clinic and FNL 115. Results showed that there is no significant association between knowledge (Tc = -0.0563, p = 0.6449) and consumption practices (Tc = 0.0919, p = 0.4895) on SSBs and the BMI of the participants. No significant association was also determined between knowledge (rb = 0.0034, p = 0.9858) and consumption practices (rb = 0.0590, p = 0.7570) and risk of comorbidities as characterized by a high WHR. Female participants are particularly vulnerable to excess SSB consumption, as it was determined that women are more likely to have a waist-to-hip ratio above WHO cut-off points. Participants consume 352 kilocalories of SSB daily on average, with most participants averaging a score of 13.1 out of 18 when testing knowledge on SSBs. Future studies are recommended to gather data from a larger sample size, utilize a different sampling method, investigate students from under-represented courses, and include physical activity as a variable.